2010
DOI: 10.1029/2009jd012535
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and diurnal variation of convective available potential energy (CAPE) using COSMIC/FORMOSAT‐3 observations over the tropics

Abstract: The global pattern of convective available potential energy (CAPE) at seasonal and diurnal time scales is discussed using 1 year of COSMIC/FORMOSAT‐3 satellite observations. The calculation of CAPE using temperature and humidity measurements of COSMIC is described. The estimated CAPE is grouped into 5 × 5 grid and is further classified into four seasons, namely, winter, spring, summer, and autumn. The CAPE magnitudes in general have high values over land as compared to oceanic region, which confirmed the consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…For example, using a tunable diode laser (TDL), Lee et al (2006) investigated the temporal variations of the vapor δ 18 O in surface air in New England and suggested that water vapor mixing ratio (w) was a better predictor for the vapor δ 18 O than the air temperature on time-scale shorter than a few days. In contrast, Wen et al (2010) found that w was a poor predictor of the temporal variability of the δ v during the peak summer monsoon activities in Beijing. Lee et al (2007) reported the continuous measurements of δ 18 O of atmospheric water vapor and ET over a temperate forest, and observed a diurnal variation of 60‰ or more of the δ 18 O flux ratio on some days.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…For example, using a tunable diode laser (TDL), Lee et al (2006) investigated the temporal variations of the vapor δ 18 O in surface air in New England and suggested that water vapor mixing ratio (w) was a better predictor for the vapor δ 18 O than the air temperature on time-scale shorter than a few days. In contrast, Wen et al (2010) found that w was a poor predictor of the temporal variability of the δ v during the peak summer monsoon activities in Beijing. Lee et al (2007) reported the continuous measurements of δ 18 O of atmospheric water vapor and ET over a temperate forest, and observed a diurnal variation of 60‰ or more of the δ 18 O flux ratio on some days.…”
Section: Introductionmentioning
confidence: 77%
“…The temporal variations of δ v near the surface are related to the atmospheric processes on various time-scales such as air mass advection, precipitation, ET and entrainment from the free atmosphere (Lai et al, 2006;Lee et al, 2006;Wen et al, 2010). Most of the seasonal variability in δ v can be understood through the Rayleigh distillation mechanisms (Gat, 1996).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations